PENERAPAN MEDIA PEMBELAJARAN APLIKASI MENTIMETER UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SMA PLUS MERDEKA SOREANG - Shafira, Shafira Yolanda Furi (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2023)
Low student learning motivation causes low learning outcomes. Learning models that are less interactive and innovative are one of the reasons students have low learning motivation. This study aims to analyze the use of learning media with the mentimeter application in Pancasila and Citizenship Education Subjects at SMA Plus Merdeka Soreang on student motivation. The research sample was taken from 30 students of Merdeka Soreang Plus High School who took Pancasila and Citizenship Education Subjects. Data collection techniques used are observation, interviews, tests, questionnaires, and documentation. The results showed changes in the increase in results and learning motivation between before and after treatment. The average learning outcomes increased from 46.87 to 70.62 with a percentage increase of 50.67%. In addition, an increase also occurred in indicators of student motivation during the learning process. The application of the meter application provides a more interactive and enjoyable learning atmosphere. This research is expected to improve the learning process by using digital media.Keyword : Mentimeter Media, Interactive Learning, Motivation